2010
DOI: 10.2298/abs1003797p
|View full text |Cite
|
Sign up to set email alerts
|

The diet of water frogs (Pelophylax esculentus 'complex') from the Petrovaradinski Rit marsh (Serbia)

Abstract: In the Petrovaradinski Rit marsh region, the composition, dynamics and importance of the food components of three syntopic anuran species of the genus Pelophylax were analyzed through all the seasons of their activity in order to determine the vulnerability of each species in the trophic competition. The results of the studies have shown that the trophic niche breadth, according to the importance index of contents, was the smallest for the species Pelophylax kl. esculentus and largest for the species Pelophyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 1 publication
2
8
3
Order By: Relevance
“…There are hemimetabolous insects (Plecoptera, Ephemeroptera, Odonata), which pass metacercariae into the imago stage (Mariluan et al, 2012) and are potentially better vectors for trematode transfer to onshorefeeding hosts, but their imago stages are rare in Pelophylax spp. diets (Tyler, 1958;Balint et al, 2008;Paunovic et al, 2010). Interestingly, infections of several plagiorchiids (Gorgodera varsoviensis, S. similis), having a second intermediate stage mainly in hemimetabolous Odonata (Sudarikov et al, 2002), had no correlation with the waterbody area in our study.…”
mentioning
confidence: 44%
“…There are hemimetabolous insects (Plecoptera, Ephemeroptera, Odonata), which pass metacercariae into the imago stage (Mariluan et al, 2012) and are potentially better vectors for trematode transfer to onshorefeeding hosts, but their imago stages are rare in Pelophylax spp. diets (Tyler, 1958;Balint et al, 2008;Paunovic et al, 2010). Interestingly, infections of several plagiorchiids (Gorgodera varsoviensis, S. similis), having a second intermediate stage mainly in hemimetabolous Odonata (Sudarikov et al, 2002), had no correlation with the waterbody area in our study.…”
mentioning
confidence: 44%
“…The fact that bre et Covaciu-Marcov et al, 2010a, 2011Ferenţi et al, 2010;Cicort-Lucaciu et al, 2011;Bogdan et al, 2012a) and in other regions (e.g. Çiçek & Mermer, 2006;Paunović et al, 2010;Mollov, 2008;Mollov et al, 2010;Kuzmin, 1990). This is more obvious for newts, which more frequently consume micro-crustaceans and Nematocera larvae (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Species consuming hard and large prey have taller and wider heads that can accommodate larger jaw muscles and increase the bite force [28,53,55]. However, studies of diet in European green frogs, including the pool frog, are limited as regards diet composition [56][57][58], with only one study analyzing prey size and its correlation with body size [59]. Studies in juvenile and adult specimens of water frogs from the Pelophylax esculentus complex showed that they have different diets [58,60], while the degree of trophic niche overlap between them indicated the existence of ontogenetic trophic niche partitioning [60].…”
Section: Discussionmentioning
confidence: 99%